Hypertension in young adults. Issue 2 (17th February 2016) - De Venecia, Toni; Lu, Marvin; Figueredo, Vincent M
ABSTRACT: Hypertension remains a major societal problem affecting 76 million, or approximately one third, of US adults. While more prevalent in the older population, an increasing incidence in the younger population, including athletes, is being observed. Active individuals, like the young and athletes, are viewed as free of diseases such as hypertension. However, the increased prevalence of traditional risk factors in the young, including obesity, diabetes mellitus, and renal disease, increase the risk of developing hypertension in younger adults. Psychosocial factors may also be contributing factors to the increasing incidence of hypertension in the younger population. Increased left ventricular wall thickness and mass are increasingly found in young adults on routine echocardiograms and predict future cardiovascular events. This increasing incidence of hypertension in the young calls for early surveillance and prompt treatment to prevent future cardiac events. In this review we present the current epidemiological data, potential mechanisms, clinical implications, and treatment of hypertension in young patients and athletes.